Author Response: Blood Neurofilament Light in Progressive Multiple Sclerosis: Post Hoc Analysis of 2 Randomized Controlled Trials. (4th October 2022) - Leppert, David; Kropshofer, Harald; Häring, Dieter; Dahlke, Frank; Patil, Ashwini; Meinert, Rolf; Tomic, Davorka; Kappos, Ludwig; Kuhle, Jens
Abstract : We thank Dr. Barro for the comment on our study. 1 We agree that batch-to-batch variability may be an important assay confounder. This was addressed in the study of 3 native serum control samples with high, medium, and low neurofilament light (NfL) chain levels. Across all measurement runs, the coefficient of variation was <15% for each of these controls. Plasma NfL was measured with the "homebrew" NfL assay, 2 which leads to higher absolute concentrations than the Quanterix NF-light (Q-NfL) assay and did not allow direct application of the age and body mass index–adjusted cutoffs established with the Q-NfL. Age was included as a covariable in all statistical models to control for its effect. 3 Therefore, the higher risk of progression in patients with a baseline NfL value >30 pg/mL shown in our results cannot be attributed to age differences and clearly supports the capacity of NfL to predict progression in patients with progressive multiple sclerosis on the group level. We agree that Z scores or percentiles based on normal controls should be preferred over the use of fixed cutoffs for optimal sensitivity of analyses. We encourage their future use, specifically in the context of individualized risk prediction of progressive disease. 3